Echo questions in Brazilian Portuguese - Kato, Mary (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
Brazilian Portuguese (BP) can have the wh-element in-situ with two types of sentence intonation: (a) the rising intonation of a yes/no question, in which case it is interpreted as an echo question, and (b) the falling intonation, similar to that of a declarative sentence, in which case it is interpreted as an ordinary question. Kato (2013) analyzed the falling intonation type as a fake wh-in-situ, with a short movement of the wh-element to a lower focus position, inspired by Miyagawa’s (2001) proposal for Japanese whereas the rising intonation type was analyzed in accordance with Kayne’s (1994) proposal, with the whole TP containing the wh-element moving to Spec of C. In this article we maintain the analysis of the wh-in-situ with falling intonation as a fake in-situ but analyze the echo question as a short yes/ no indirect question. The languages used to support this analysis of BP are English, French, and Japanese.